Television, Tabloids, and Tears : Fassbinder and Popular Culture. - Shattuc, Jane (University of Minnesota Press, 1995)
I am Biberkopf, Rainer Werner Fassbinder declared, aligning himself with the protagonist of his widely seen television adaptation of Berlin Alexanderplatz. The statement provoked an unprecedented national debate about what constituted an acceptable German artist and who has the power to determine art. More than any recent German director, Fassbinder embodied this debate, and Jane Shattuc shows us how much this can tell us, not just about the man and his work, but also about the state of "culture" in Germany. It is fascinating in itself that Fassbinder, a highly controversial public f.